Unlocking Firm Value through Green Accounting: Insights from the Energy Industry - Mawarni, Alberti Listia Tri; Kurniawati, Estetika Mutiaranisa; Widjajanto , Anis (JIFA (Journal of Islamic Finance and Accounting), 2024)
This study aims to assess the impact of green accounting on the firm value of energy sector companies listed on the Indonesia Stock Exchange (IDX). This research employs a quantitative methodology utilizing purposive sampling. The research focuses on companies engaged in the Environmental Performance Rating Program (PROPER). The data sample comprises 28 companies from the energy sector spanning the years 2018 to 2022. The independent variable in this study is green accounting, assessed through environmental cost, environmental disclosure, environmental performance, and environmental committee. The dependent variable is the firm's value as indicated by Tobin's Q formula. This study employs multiple linear regression analysis utilizing the SPSS Statistics 26 software. This study's findings demonstrate that environmental costs and scores do not influence firm value. Nonetheless, environmental performance and the environmental committee positively impact firm value. We expect this research to illuminate the importance and effectiveness of green accounting in sustainability reports, allowing companies to improve their social and environmental accountability through the adoption of environmental management programs.